2015
DOI: 10.1039/c4cp05766j
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of the effect of molecular weights of polyvinyl alcohol on polyvinyl alcohol–graphene oxide composite hydrogels

Abstract: Polyvinyl alcohol (PVA) hydrogels have been proposed for use as promising biomaterials in biomedical and tissue engineering, and graphene oxide (GO) has been recognized as a unique two-dimensional building block for various graphene-based supramolecular architectures. In this article, we systematically studied the influence of three kinds of PVA with different molecular weights on the interaction between PVA and GO. Moreover, the effects of PVA on the gelation of GO were also investigated. The native PVA hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 45 publications
(48 reference statements)
1
37
0
Order By: Relevance
“…The evolution of the dehydration process can be followed by changes in the vibrational bands corresponding to H-O and C=O bonds of the polymer, but also following the peaks corresponding to water molecules involved in various types of hydrogen bonding. The authors found that the polymer network shrinks with water evaporation and at the end in the gel the residual water forms a tetragonal structure [28]. Similar behaviour on dehydration has been noticed for all polymeric systems [38][39][40].…”
Section: Raman Spectroscopysupporting
confidence: 53%
See 2 more Smart Citations
“…The evolution of the dehydration process can be followed by changes in the vibrational bands corresponding to H-O and C=O bonds of the polymer, but also following the peaks corresponding to water molecules involved in various types of hydrogen bonding. The authors found that the polymer network shrinks with water evaporation and at the end in the gel the residual water forms a tetragonal structure [28]. Similar behaviour on dehydration has been noticed for all polymeric systems [38][39][40].…”
Section: Raman Spectroscopysupporting
confidence: 53%
“…IR spectroscopy can be a method for the investigation of these hybrid materials. In a systematic study on the poly(vinyl alcohol) (PVA)/ graphene oxide composite hydrogels, Xue and co-workers [28] noticed that an increase of the PVA molecular weight favours the formation of hydrogels containing GO. GO contains various oxygen functional groups (e.g.…”
Section: Ir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This increased strength may be attributed to increased hydrogen bonding and entanglement between the polymer chains. [ 60,66 ] However, increasing the molecular weight further to 202 000 g mol −1 lead to a decrease in strength outside of the cartilage‐equivalent range because the higher molecular weight polymer did not fully dissolve during the infiltration processes. Compositions with PVA below 40 wt% were not cartilage equivalent, while higher concentrations did not fully dissolve during infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…In this direction, hydrogels are designed in order to obtain mechanical properties suitable to different application in many fields like drug delivery and tissue engineering [3][4][5] . Due to their remarkable characteristics like tunable physical, chemical, and biological properties, high biocompatibility and versatility in fabrication hydrogels have emerged as promising materials in the biomedical field [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%